Răspuns :
mai intai inmultesti totul cu 7
dupa il treci pe 6 din partea stanga in partea dreapta
o sa-ti dea 4/3 x (5 + (x-1)/2)=8
inmultesti cu 3/4
5 + (x-1)/2=6
(x-1)/2=6-5=1
inmultesti cu 2
x-1 = 2 de unde x=3
dupa il treci pe 6 din partea stanga in partea dreapta
o sa-ti dea 4/3 x (5 + (x-1)/2)=8
inmultesti cu 3/4
5 + (x-1)/2=6
(x-1)/2=6-5=1
inmultesti cu 2
x-1 = 2 de unde x=3
[tex] \frac{1}{7}( \frac{4}{3}( 5+ \frac{x-1}{2})+6)=2 \Rightarrow \frac{1}{7}( \frac{4}{3}( \frac{10+x-1}{2})+6) = 2 \Rightarrow \\ \\ \Rightarrow \frac{1}{7}( \frac{4}{3}( \frac{9+x}{2})+6) = 2 \Rightarrow \frac{1}{7}( \frac{36+4x}{6}+6)=2 \Rightarrow \\ \\ \Rightarrow \frac{36+4x}{42}+ \frac{6}{7}=2 \Rightarrow 36+4x+6\cdot6=2\cdot42 \Rightarrow4x = 84-36-36 \Rightarrow \\ \\ \Rightarrow4x = 84-72 \Rightarrow4x = 12 \Rightarrow x = \frac{12}{4}\Rightarrow x = 3 [/tex]